2018
DOI: 10.1080/13814788.2018.1491964
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual aids in primary healthcare settings’ waiting rooms. A systematic review

Abstract: Background: Health promotion is part of GPs' commitments. Some waiting rooms have therefore been implemented with audiovisual aids (posters, pamphlets or screens) for health promotion purposes. Few studies have assessed the effect of audiovisual aids in primary care.Objectives: To identify, describe and appraise studies that have investigated the effects of audiovisual aids on health promotion in primary healthcare waiting rooms. To determine which factors influence this impact through literature review.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
(79 reference statements)
1
26
0
Order By: Relevance
“…This campaign directly targeted only part of the patient‐clinician dyad. However, posters can raise awareness among clinicians indirectly, 8 and the campaign was designed to target clinicians indirectly via discussions with the patient. Future work could explore whether this happens in practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This campaign directly targeted only part of the patient‐clinician dyad. However, posters can raise awareness among clinicians indirectly, 8 and the campaign was designed to target clinicians indirectly via discussions with the patient. Future work could explore whether this happens in practice.…”
Section: Discussionmentioning
confidence: 99%
“…One simple, scalable and under‐investigated approach to reducing medical overuse is a public health campaign displayed in health service waiting rooms. A systematic review 8 of observational and intervention studies found that interventions using waiting room screens (eg TV, tablet, computer) can enhance knowledge about cancer screening, influenza vaccination and contraception in women. However, effects on health behaviour were unclear.…”
Section: Introductionmentioning
confidence: 99%
“…They found evidence for knowledge improvement, yet no evidence of impact on health behaviours or attitudes, but there were a number of methodological limitations noted. 24 There is a paucity of research investigating the impact of education in waiting rooms related to CVD prevention and CPR training. A small study (n=100) in an emergency department waiting room found participants exposed to a 1-minute video were more likely to perform CPR correctly, indicating such interventions may be feasible and effective for CVD prevention as well.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…They found evidence for knowledge improvement, yet no evidence of impact on health behaviours or attitudes, but there were a number of methodological limitations noted. 24 …”
Section: Introductionmentioning
confidence: 99%
“…These roles include ‘show and tell’ tutorials, imparting scientific knowledge to healthcare professionals, students and patients, aiding in the decision-making process of physicians as well as patients, curbing misinformation, documentation of processes, performance review, visual argumentation, and fast dissemination of results. 14 15 16 17 18 19 20 VAs are inherently better for portraying information like medical procedures and patient interviews in qualitative research. 20 The Journal of Visualized Experiments (Cambridge, MA, USA), launched in 2006, with more than 10,000 published videos, is the first peer reviewed scientific video journal, describing new laboratory methods, science concepts and protocols from all over the world in video format to improve the reproducibility of experiments in life sciences and physics.…”
Section: Introductionmentioning
confidence: 99%